(3eHGOjA cjejGA Gdce (B/ s - (3hGUd, eMeO eLOjs ((3GdbGgQI (B[(3eUQ(B] : s (3OGQ GdfTQ ddLGeYGJ,s, 2008)
(3fXQjI ejcGfjcG Gdce gj GdGSGS GdPj jecf JWHjbg Ydi GdGLSGe eJffGgjI GdUZQ hGjVG Ydi GdGLSGe GdcHjQI MjK Gf GdejcGfjcG GdcdGSjcjI gj MGdI NGUI ef GdfXQjI GdYGeI (B"(3ejcGfjcG Gdce(B"s (3hGdgOa GdGSGSj dcjejGA Gdce gh TQM hage fJGFL GdJLGQH GdYdejI hGjVG deYQaI GecGfjI MOhK GdJZjQ GdcjejGFj Ge dG(B.s
(3jJVef bGFeI HGdeUWdMGJ GdYdejI, GfcdjRj YQHj, UaMI(B167-179.s
(3jJVef edGMb(B.s
(3jJVef GQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdcjejGA GdcejIs